HUBUNGAN DUKUNGAN ORGANISASIONAL DAN KUALITAS HIDUP KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL PEMEDIASI - Arik Nur Cahyo; Woro Utari; Indra Prasetyo (Universitas Triatma Mulya, 2023)
The purpose of this study, among others, is to describe organizational citizenship behavior, work engagement, organizational support and quality of work life of employees at the Public Works Department of Highways and Spatial Planning, Bojonegoro Regency. To analyze the effect of organizational support and quality of work life on work engagement, the effect of organizational support and quality of work life and work engagement on organizational citizenship behavior, the effect of organizational support and quality of work life on organizational citizenship behavior through work engagement. This type of research uses explanatory research with a quantitative research approach. The population in this study were all employees of the Public Works Department of Highways and Spatial Planning of Bojonegoro Regency with the status of PNS with a total of 52 people. The sample in this study were 52 people with the sampling technique used in this study was census sampling. Methods of data collection using questionnaires and documentation. Methods of data analysis using descriptive statistics and hypothesis testing of this study using analytical techniques using SEM with the alternative method of PLS. The results showed that organizational citizenship behavior, work engagement, organizational support and quality of work life of employees at the Public Works Department of Highways and Spatial Planning in Bojonegoro Regency were in the high category. Organizational support for work engagement has a positive and insignificant effect, quality of work life on work engagement has a significant effect, organizational support for OCB has a significant influence. Quality of work life on OCB has a significant effect, work engagement on OCB has a significant effect. Organizational support for OCB through work engagement has an insignificant effect. Quality of work life on OCB through work engagement has a significant effect